Analytical Technique Based on New sub-ODE Method for Finding New Optical Solitons and Other Solutions for Lakshmanan-Porsezian-Daniel (LPD) Model (Journal of Humanitarian and Applied Sciences, 2023)
Solitons and other solutions are revealed for the Lakshmanan-Porsezian-Daniel model in birefringent fibers with the aid of the new sub-ODE method. The prosidure reveal dark and bright soliton solutions, periodic, rational, Weierstrass and Jacobian elliptic function solutions.
Keywords: Birefringent fibers; Lakshmanan-Porsezian-Daniel mode; new sub-ODE; optical solitons